Mechanisms of Life History Evolution : The Genetics and Physiology of Life History Traits and Trade-Offs - Flatt, Thomas and Andreas Heyland; Edited by Flatt, Thomas and Heyland, Andreas (Oxford Oxford Univ. Press, 2012)
This interdisciplinary volume unites evolutionary and molecular biologists from various fields (life history theory, molecular biology, developmental biology, aging, phenotypic plasticity, social behaviour, and endocrinology) who use studies of molecular mechanisms to solve fundamental questions in life history evolution in a variety of organisms
Include Reference and Index
Keywords: Evolutionary genetics -- Life cycles (Biology)